The Synovium Attenuates Cartilage Degeneration in KOA through Activation of the Smad2/3-Runx1 Cascade and Chondrogenesis-related miRNAs - Xiaoyi Zhao; Fangang Meng; Shu Hu; Zibo Yang; Hao Huang; Rui Pang; Xingzhao Wen; Yan Kang; Zhiqi Zhang (Elsevier, 2020)
Knee osteoarthritis (KOA) is a highly prevalent disabling joint disease in aged people. Progressive cartilage degradation is the hallmark of KOA, but its deeper mechanism remains unclear. Substantial evidence indicates the importance of the synovium for joint homeostasis. The present study aimed to determine whether the synovium regulates cartilage metabolism through chondrogenesis-related microRNAs (miRNAs) in the KOA microenvironment. Clinical sample testing and in vitro cell experiments screened out miR-455 and miR-210 as effective miRNAs. The levels of both were significantly reduced in KOA cartilage but increased in KOA synovial fluid compared with controls. We further revealed that transforming growth factor β1 (TGF-β1) can significantly upregulate miR-455 and miR-210 expression in synoviocytes. The upregulated miRNAs can be secreted into the extracellular environment and prevent cartilage degeneration. Through bioinformatics and in vitro experiments, we found that Runx1 can bind to the promoter regions of miR-455 and miR-210 and enhance their transcription in TGF-β1-treated synoviocytes. Collectively, our findings demonstrate a protective effect of the synovium against cartilage degeneration mediated by chondrogenesis-related miRNAs, which suggests that Runx1 is a potential target for KOA therapy.